'We had to do what we thought was right at the time': retrospective discourse on the 2009 H1N1 pandemic in the UK. Issue 3 (20th August 2013) - Davis, Mark; Flowers, Paul; Stephenson, Niamh
Abstract For a few weeks in 2009 it was not certain whether the world faced a lethal influenza pandemic. As it turned out, the H1N1 pandemic was less severe than anticipated, though the infection did affect groups not usually susceptible to influenza. The deep uncertainties of this pandemic moment were associated with immense practical, scientific and political challenges for public health agencies around the world. We examine these challenges by drawing on the sociology of uncertainty to analyse the accounts given by UK public health practitioners who managed local responses to the pandemic. We discuss the retrospective and mitigating discourse; 'we had to do what we thought was right at the time', used by interviewees to explain their experience of articulating plans for a severe pandemic influenza with one that turned out to be mild. We explore the importance of influenza's history and imagined future for pandemic management and, relatedly, how pandemic response and control plans disrupted the normal ways in which public health exercises its authority. We conclude by suggesting that difficulties in the management of pandemic influenza lie in its particular articulation of precautions, that is, securing a safe future against that which cannot be predicted.